Takhrij and Syarah Hadith of Chemistry: Removing Rust On Iron - Fauziyyah Nabilah Duwila; Irfan Alfiansyah; Assyifa Junitasari; Cucu Setiawan; Iu Rusliana (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the prophet Saw. about iron. This method of research is qualitative through the takhrij and syarah hadith approaches a chemical analysis. The results and discussions of this research are ways of eliminating and preventing rusty iron. The conclusion of this research is takhrij and syarah hadith of the prophet Saw. about iron by chemical analysis in optimizing iron use with plans to prevent it.